SLEMAN TOURISM VILLAGE CLASSIFICATION 2016 - Muhammad Dzulkifli; Milawaty; Uystka Hikmatul Kamiliyah NH; Lely Dian Utami (STABN Raden Wijaya Wonogiri, 2025)
Sleman Regency is one of the areas that has the potential for alternative tourism activities. Thus, the development of tourist attractions in this district needs to be considered, especially related to cultural diversity and natural uniqueness. In 2016, the Department of Culture and Tourism of the Sleman Regency held a classification activity for the Sleman Regency Tourism Village. A total of 39 Tourism Villages in Sleman Regency participated in this program. This classification program is expected to motivate the community to build a tourism village. Furthermore, it is also an effort to evaluate and improve competitiveness between tourism villages in Sleman Regency. Another purpose of the classification is to identify the distribution of tourism villages in Sleman as well as to categorize the level of tourism villages based on their development. The research data were collected through interviews, documentation, observation, and using an assessment instrument with 8 (eight) indicators that had been agreed upon by a team of experts as well as the Department of Culture and Tourism. The data were analyzed using simple interval calculations strengthened by a qualitative description of the field observation results. The analysis results show that the classification of Tourism Villages in Sleman Regency in 2016 is divided into three categories, namely the Growing Category, the Developing Category, and the Independent Category of Tourism Villages. Based on the results of the conducted classification, from the 39 classified tourism villages, 14 villages belong to the growing category, 8 villages belong to the developing category, and 9 villages belong to the independent category. In addition, there are 8 villages that are considered unqualified as tourism villages. Keywords: classification, tourism village, Sleman, Yogyakarta, 2016